Engineering transverse cell deformation of bamboo by controlling localized moisture content - Tian Bai; Jie Yan; Jiqing Lu; Jie Zhou; Hang Yao; Xiuwen He; Shaohua Gu; Zhihan Tong; Sheldon Q. Shi; Jian Li; Wanli Cheng; Dong Wang; et al. (Nature Communications)
Abstract Bamboo’s native structure, defined by the vertical growth pattern of its vascular bundles and parenchyma cell tissue, limits its application in advanced engineering materials. Here we show an innovative method that controls localized moisture content to shape natural bamboo into a versatile three-dimensional (3D) structural product. Different temperatures along the transverse direction of bamboo were used to induce directional water transport within the bamboo, so that the distribution of internal stress was shifted from the bamboo surface to the inner layers. The internal stress shifting enabled the control of the transverse deformation. After densification, a 3D-molded bamboo product was obtained that retained the natural heterogeneous structure. The molded bamboo had a high specific strength of 740.58 MPa·kg−1·m3 and impact resistance of 2033.29 J/m, surpassing most renewable and nonrenewable engineering materials. The life cycle assessment revealed that replacing metals and polymers in structural materials with 3D-molded bamboo significantly reduces carbon emissions. Our proposed “localized moisture gradient-driven uneven drying” strategy represents a sustainable path in transforming natural bamboo into high-performance engineering materials.